Excess mortality in persons with severe mental disorder in Sweden: a cohort study of 12 103 individuals with and without contact with psychiatric services - Tidemalm, Dag (BioMed Central, 2008)
BACKGROUND: Investigating mortality in those with mental disorder is one way of measuring effects of mental health care reorganisation. This study's aim was to investigate whether the excess mortality in those with severe mental disorder remains high in Sweden after the initiation of the Community Mental Health Care Reform. We analysed excess mortality by gender, type of mental health service and psychiatric diagnosis in a large community-based cohort with long-term mental disorder. METHODS: A survey was conducted in Stockholm County, Sweden in 1997 to identify adults with long-term disabling mental disorder (mental retardation and dementia excluded). The 12 103 cases were linked to the Hospital Discharge Register and the Cause of Death Register. Standardised mortality ratios (SMRs) for 1998–2000 were calculated for all causes of death, in the entire cohort and in subgroups based on treatment setting and diagnosis. RESULTS: Mortality was increased in both genders, for natural and external causes and in all diagnostic subgroups. Excess mortality was greater among those with a history of psychiatric inpatient care, especially in those with substance use disorder. For the entire cohort, the number of excess deaths due to natural causes was threefold that due to external causes. SMRs in those in contact with psychiatric services where strikingly similar to those in contact with social services. CONCLUSION: Mortality remains high in those with long-term mental disorder in Sweden, regardless of treatment setting. Treatment programs for persons with long-term mental disorder should target physical as well as mental health.